Challenges and strategies of the neonatal intensive nursing team against the Covid-19 pandemic (Research, Society and Development, 2022)
Objective: To analyze the strategies adopted by the nursing team of a Neonatal Intensive Care Unit in the face of the Covid-19 pandemic, as well as to discuss the main challenges that the pandemic scenario has brought to professional practice. Methodology: descriptive-exploratory research, of a qualitative nature, developed through semi-structured interviews among 18 nurses and nursing technicians from a public institution. The analysis was based on the thematic analysis technique. Results: The participants revealed different challenges, such as the lack of personal protective equipment, space/structure in the sector, knowledge related to the disease and devaluation of the professional category. It was also observed that some professional strategies, such as strengthening teamwork and strengthening prevention measures, stood out even more in the pandemic scenario. Conclusion: The nursing team encountered new challenges for professional practice. Other than that, challenges that were already common, such as the lack of resources and materials, were reflected in the emotional responses of professionals. On the other hand, some professional strategies stood out even more, an extremely positive aspect for professional and patient safety.